MEMBANGUN BUDAYA BIROKRASI UNTUK GOOD GOVERNANCE - Hadian , Dedi (Majalah Bisnis & IPTEK, 2021)
In the future government organizations need for a total change that which can be implemented in a gradual implementation that starts at the central level to the local level. For the effectiveness of the change of government organizations need for strong political will and political courage to undertake concrete actions. So the urgency of building a culture of bureaucracy for good governance is a must. Keywords: government organizations; culture of the organization; governance